28u-8+u+32=40u-9

Simple and best practice solution for 28u-8+u+32=40u-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 28u-8+u+32=40u-9 equation:


Simplifying
28u + -8 + u + 32 = 40u + -9

Reorder the terms:
-8 + 32 + 28u + u = 40u + -9

Combine like terms: -8 + 32 = 24
24 + 28u + u = 40u + -9

Combine like terms: 28u + u = 29u
24 + 29u = 40u + -9

Reorder the terms:
24 + 29u = -9 + 40u

Solving
24 + 29u = -9 + 40u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-40u' to each side of the equation.
24 + 29u + -40u = -9 + 40u + -40u

Combine like terms: 29u + -40u = -11u
24 + -11u = -9 + 40u + -40u

Combine like terms: 40u + -40u = 0
24 + -11u = -9 + 0
24 + -11u = -9

Add '-24' to each side of the equation.
24 + -24 + -11u = -9 + -24

Combine like terms: 24 + -24 = 0
0 + -11u = -9 + -24
-11u = -9 + -24

Combine like terms: -9 + -24 = -33
-11u = -33

Divide each side by '-11'.
u = 3

Simplifying
u = 3

See similar equations:

| -9x+5x=8 | | 3x+6(9x-7)=414 | | 4r+11=15 | | 2*-13-3-15=9 | | 2x-39=17 | | 4p+15+33=6p | | -(-8)+4=2(x)+-8 | | 15w-49+33=13w | | -8/3x=16/3 | | 49x+43=48x+45 | | z-32.56=12 | | -12x-14=-86 | | 2z+47=6z-16 | | 2(12y-11)=-4(1-6y) | | -(x-8)+4=2(12)+x | | 25=10+5j | | 5m^2+26m+5=0 | | 2x-3*-13=9 | | -(x-8)+4=2(-12)+x | | 7x+3(5-3x)=5 | | b+3+b=b+50 | | ly-8l+6=15 | | 3a+1=a+19 | | 15.08+w=30.08 | | Cosx/cos^2(2x) | | -5x-3*-13=30 | | 7m+48=8(m+7) | | 3b^2+11b+8=0 | | -5x-(3*-13)=30 | | 18=5-2+6x-x | | -(x-8)+4=2(7)+x | | x+14=35 |

Equations solver categories